DRYING OF EGGPLANT SLICES IN THIN LAYERS AT DIFFERENT AIR TEMPERATURES - Doymaz, Ibrahim (WILEY-BLACKWELL, 2011)
The effect of water-blanching treatment and air temperature on drying kinetics of eggplant slices were investigated at air temperatures (50, 60, 70 and 80C). Both the blanching and air temperature influenced the drying time of eggplant slices. Moisture ratios were fitted to 11 different mathematical models using nonlinear regression analysis. The regression results showed that the logarithmic, Wang and Singh, and Midilli et al. models satisfactorily described the drying behavior of eggplant slices with highest R2 value and lowest chi 2, root mean square error and residual sum of squares values. The effective moisture diffusivity increases as temperature increases and range between 5.575 and 9.745 x 10-10 m2/s for unblanched samples, and between 5.851 and 11.077 x 10-10 m2/s for blanched samples. The activation energy values of unblanched and blanched samples were estimated to be 18.27 and 20.76 kJ/mol, respectively. PRACTICAL APPLICATIONS In this study, a laboratory convective hot-air dryer was used for the thin-layer drying of blanched/unblanched eggplant slices and experimental moisture ratio was compared with 11 thin-layer drying models. The blanching treatment followed by hot-air drying may provide a practical method for the preservation of eggplant and the production of dried eggplant slices. The dried product is a valuable ingredient in the preparation of soups, premixed foods, etc.
Keywords: RED BELL PEPPER; BED DRYER; HOT-AIR; KINETICS; STORAGE; LEAVES; FRUIT; L.; DEHYDRATION; PARAMETERS; Food Science & Technology